Aspek Fiskal dan Faktor Sosial dalam Pembangunan Ekonomi Inklusif di Kawasan Barat dan Timur Indonesia - Junaidin, Junaidin (Indo-MathEdu Intellectuals Journal, 2026)
Inclusive economic development is an important indicator for assessing the extent to which the development process is able to reach and provide benefits evenly to all levels of society and regions. This study aims to analyze the potential influence of education expenditure, health expenditure, average length of schooling, and adequate sanitation on inclusive economic development in Western and Eastern Indonesia during the period 2019–2023. This study uses a quantitative approach with a binary logistic regression method, which is applied to identify the opportunities of each independent variable in enhancing inclusive economic development. The results of the analysis show that health expenditure, average length of schooling, and adequate sanitation have a positive effect and provide significant opportunities for increasing inclusive economic development. Conversely, education expenditure has a negative effect and does not provide significant opportunities for inclusive economic development. These findings indicate that improving the quality of health, education through longer schooling, and access to proper sanitation play an important role in promoting more inclusive economic development, while the effectiveness of education expenditure needs to be further reviewed in order to have an optimal impact